The inaccurate citation of the “Universal Declaration of Animal Rights” (UDAR) in the scientific literature: a scoping review - Alexandre Azevedo; Martin Whiting; Manuel Magalhães-Sant’Ana (BMC Veterinary Research)
Abstract Background The Universal Declaration of Animal Rights (UDAR), adopted in 1977 by an international NGO inspired by the Universal Declaration of Human Rights and made public the following year, aimed to establish a universal code for human conduct toward animals. The declaration was revised twice, in 1989 and 2018, but it failed to be internationally recognised or adopted. While its global influence remained limited, misinterpretations of its scope and context have proliferated in legal and veterinary documents. To gauge its impact on scientific literature, a scoping review across three databases (Scopus, Web of Science Core Collection, and Google Scholar) was conducted for publications citing the UDAR from 1979 to 2022. Results In terms of research field, the UDAR is mostly cited in the fields of law (27%), philosophy, ethics, and religion (17%), clinical medicine (17%), and basic medicine (11%). The 1978 UDAR version was most often cited. Among 305 screened publications, 47.9% contained erroneous or misleading claims about the UDAR. Common errors included linking the UDAR to UNESCO (34.8%) and conferring it universal endorsement or legally binding value (10.2%). More than half (57%, 59/103) of the mentions in the ethics section contained errors, namely confusing UDAR with other animal protection texts. Regarding the type of animal use, most misleading claims were found in scientific publications focusing on the use of animals in research. Conclusions The misappropriation of the UDAR risks providing a false sense of legitimacy and moral compass to editors, reviewers, and readers regarding animal use and highlights that the authors are unaware of ethical or regulatory frameworks governing the proper use of animals in science. This is particularly relevant because the 1978 version, which is antithetical to animal use in science, was most often cited, raising concerns about the governance of animal research in some institutions and the efficacy of the peer review process in detecting these errors. Finally, UDAR mentions grew more than the estimated growth of scientific publications worldwide, thus suggesting an increase in its influence.